What factors drive inequalities in carbon tax incidence? Decomposing socioeconomic inequalities in carbon tax incidence in Ireland - Niall Farrell (The Economic and Social Research Institute (ESRI), 2015)
Carbon taxes increase the cost of necessary household energy expenditures. In many developed countries, carbon taxes are regressive as they comprise a greater proportion of a poorer household's income. Certain socioeconomic groups are more negatively affected by these impacts than others. While inequality of incidence by income group has received great attention in the literature, a gap exists to quantify the inequality associated with socioeconomic characteristics. This information is policy-relevant as it may inform the most effective means to offset negative welfare impacts through changes to taxes and/or social transfers. This paper provides this contribution. First, the inequality of carbon tax incidence across the income spectrum is quantified using the concentration index methodology. A subsequent multivariate decomposition quantifies the contribution each socioeconomic factor makes towards this inequality of incidence. This is carried out for electricity, motor fuel and all other home fuels to elicit variation of socioeconomic incidence by source. While income contributes a great deal towards inequality of incidence for other home fuels, socioeconomic characteristics are the primary determinants of electricity and motor fuel-related carbon tax incidence. The relative importance of each characteristic in determining regressive impacts is quantified and this varies by carbon tax source.
Keywords: 330; Carbon tax; Inequality; Socioeconomic Determinants; Concentration Index